Policing intimacy : law, sexuality, and the color line in twentieth-century hemispheric American literature - Sciuto, Jenna Grace (Jackson : University Press of Mississippi, 2021)
"In Policing Intimacy: Law, Sexuality, and the Color Line in Twentieth-Century Hemispheric American Literature, author Jenna Grace Sciuto analyzes literary depictions of sexual policing of the color line across multiple spaces with diverse colonial histories: Mississippi through William Faulkner's work, Louisiana through Ernest Gaines's novels, Haiti through the work of Marie Chauvet and Edwidge Danticat, and the Dominican Republic through writing by Julia Alvarez, Junot Díaz, and Nelly Rosario. This literature exposes the continuing coloniality that links depictions of US democracy with Caribbean dictatorships in the twentieth century, revealing a set of interrelated features characterizing the transformation of colonial forms of racial and sexual control into neocolonial reconfigurations. A result of systemic inequality and large-scale historical events, the patterns explored herein reveal the ways in which private relations can reflect national occurrences and the intimate can be brought under public scrutiny. Acknowledging the widespread effects of racial and sexual policing that persist in current legal, economic, and political infrastructures across the circum-Caribbean can in turn bring to light permutations of resistance to the violent discriminations of the status quo. By drawing on colonial documents, such as early law systems like the 1685 French Code Noir instated in Haiti, the 1724 Code Noir in Louisiana, and the 1865 Black Code in Mississippi, in tandem with examples from twentieth-century literature, Policing Intimacy humanizes the effects of legal histories and leaves space for local particularities. By focusing on literary texts and variances in form and aesthetics, Sciuto demonstrates the necessity of incorporating multiple stories, histories, and traumas into accounts of the past"--
"We will have to wait": racial hierarchies, plantation intimacy, and sexual policing in William Faulkner's Mississippi -- "There is no in-between": community, sexuality, and the shifting construction of race in Ernest Gaines's Louisiana -- "They were starting something": race, gender, and failed revolution in Ernest Gaines's Of Love and Dust -- "For fear of a scandal": Sexual control, racism, and the public nature of private relations in Marie Chauvet's twentieth-century Haiti -- "We are trawling in silences here": race, sexuality, and unnarratable histories in literary depictions of Dominican dictatorship -- Coda: Looking back in resistance, looking to the present.
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on April 29, 2021).
JSTOR
Keywords: Race discrimination; Sex discrimination; Racism in literature; Sex in literature; Discrimination raciale; Discrimination sexuelle; Racisme dans la littérature.; Sexualité dans la littérature.; racial discrimination; sex discrimination; Regional; American; LITERARY CRITICISM; Caribbean & Latin American; Women's Studies; SOCIAL SCIENCE; Race discrimination; Racism in literature; Sex discrimination; Sex in literature; Literary criticism; Literary criticism; Critiques littéraires.